Peranan Guru dalam Mengatasi Anak Pemalu di RA Darussalam Pangandaran - Indah Permata Sholihah; Desi Intan Permatasari; Yuyun Rahayu (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Shy children are one of the attitudes that often occur in every school. Shame in children is a negative emotion that can have a negative impact on children's social and emotional development. One of the developments that can be hampered is lack of self-confidence, not wanting to hang out with friends and being a quiet person. In the research that we conducted at RA Darussalam, there were some shy children. The research was conducted at RA Darussalam in August 2022. The method used was the conversational method. This study aims to describe the role of teachers in shy children. The results of the observations show that there are shy children in grades A and B. What we can do as practical teachers in dealing with shy children are; 1) Approach the child to talk to. 2) Look at him when he talks and get the child to look at us. 3) Ask him what he likes 4) Ask him what he wants at the time.